1964
DOI: 10.1084/jem.120.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bacterial Endotoxin on Rabbit Platelets

Abstract: The platelet injury produced by bacterial endotoxin and thrombin have been compared in studies utilizing citrated rabbit platelet-rich plasma. Endotoxin-induced platelet injury is characterized by a lag period, is progressive, and does not produce gross clot formation. Thrombin-induced platelet injury is immediate, non-progressive, and is associated with clot formation. The quantity of thrombin required to produce clot formation in this citrated system is less than that required to produce release of platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1966
1966
1993
1993

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…While a superficially similar form of platelet aggregation and release of platelet factors is produced by thrombin, previous studies have shown that the effects of endotoxin and of thrombin on platelets differ in several important respects (6). The blood of most mammals contains antibodies to endotoxin (7).…”
mentioning
confidence: 99%
“…While a superficially similar form of platelet aggregation and release of platelet factors is produced by thrombin, previous studies have shown that the effects of endotoxin and of thrombin on platelets differ in several important respects (6). The blood of most mammals contains antibodies to endotoxin (7).…”
mentioning
confidence: 99%
“…In vitro studies with rabbit platelets have shown that relatively small concentrations of heparin are capable of preventing thrombin induced-platelet injury whereas very large amounts of the anticoagulant are necessary to prevent similar damage by bacterial endotoxin (1). In vivo investigations have demonstrated that the usual anticoagulating amounts of heparin do not prevent the thrombocytopenia in the generalized Shwartzman reaction (gSr) ( 2 ) in rabbits and a similar phenomenon has been observed in humans with septic shock treated with heparin (3,4).…”
mentioning
confidence: 85%
“…Previous studies have demonstrated that 5-hydroxytryptamine (5HT) released from blood platelets by bacterial endotoxin (lipopolysaccharide; LPS) requires the presence of calcium ion and plasma factor and that heparin inhibits its release (1)(2)(3)(4)(5). Recently, Nomura and Takagi (6) have separated the 5HT releasing factor from rabbit plasma by gel filtration on a Sephadex G-150 column.…”
mentioning
confidence: 99%